Deep mowing rather than fire restrains grassland Miscanthus growth via affecting soil nutrient loss and microbial community redistribution - Mao, Zhuxin; Wang, Yuchao; Li, Qian; Li, Weimin; Wang, Hong; Li, Yang; Yue, Ming (Frontiers in Plant Science, 2023)
Fire and mowing are crucial drivers of grass growth. However, their effects on soil properties, microbial communities, and plant productivity in dry-alkaline grasslands have not been well investigated. This study evaluated the effects of mowing (slightly and deeply) and fire on vegetation traits (Tiller number per cluster and plant height) and biomass (plant dry weight), and soil availability of N, P, and K, as well as soil microorganism abundance in a Miscanthus system. We designed one control and three experimental grass plots (slightly and deeply mowed, and burned) in 2020–2021 in the Xi'an Botanical Garden of Shaanxi Province, Xi'an, China. Tiller number, plant height per cluster, and soil N, P, and K availability during Miscanthus growth decreased significantly (p < 0.05) in all treatments compared to the control. However, this effect was much greater in the deep-mowing plot than in the other plots. After harvest, deep mowing induced the greatest effect on biomass among all treatments, as it induced a 5.2-fold decrease in dry biomass relative to the control. In addition, both fire and mowing slightly redistributed the community and diversity of the soil bacteria and fungi. This redistribution was significantly greater in the deep-mowing plot than in other plots. In particular, relative to the control, deep mowing increased the abundance of Firmicutes and especially Proteobacteria among soil bacterial communities, but significantly (p < 0.05) decreased Basidiomycota and increased Ascomycota abundance among soil fungal communities. We conclude that nutrient limitation (N, P, and K) is crucial for Miscanthus growth in both mowing and fire grasslands, whereas deep mowing can induce soil nutrient loss and microorganism redistribution, further restraining grass sustainability in dry-alkaline grasslands.